2023
DOI: 10.3390/tropicalmed8050283
|View full text |Cite
|
Sign up to set email alerts
|

Infective Endocarditis due to Non-HACEK Gram-Negative Bacilli: Clinical Characteristics and Risk Factors from a Prospective Multicenter Brazilian Cohort

Abstract: Background: Non-HACEK Gram-negative bacilli (NGNB) infective endocarditis (IE) has a growing frequency. We aimed to describe cases of NGNB IE and find associated risk factors. Methods: We conducted a prospective observational study of consecutive patients with definitive IE according to the modified Duke criteria in four institutions in Brazil. Results: Of 1154 adult patients enrolled, 38 (3.29%) had IE due to NGNB. Median age was 57 years, males predominated, accounting for 25/38 (65.8%). Most common etiologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…However, a recent study across 13 hospitals in Pennsylvania, USA (26), identified 123 cases through electronic records between April 2010 and December 2021, and found a high proportion of intravenous drug users (52%) and of S.marcescens, similar to older series from the 80's and 90's in which drug users prevailed. Other series of non-HACEK Gram negative IE did not show a predominance of S.marcescens nor of P.aeruginosa; E.coli and K.pneumoniae figure more frequently or just as frequently as these do (25,(27)(28)(29)(30)(31)(32)(33)(34). Although it is positive to stimulate clinicians to think of IE and pursue the diagnosis with TOE or PET CT, this will add a great deal of cost and invasive procedures.…”
Section: Gphysical Examination Criteriamentioning
confidence: 97%
See 1 more Smart Citation
“…However, a recent study across 13 hospitals in Pennsylvania, USA (26), identified 123 cases through electronic records between April 2010 and December 2021, and found a high proportion of intravenous drug users (52%) and of S.marcescens, similar to older series from the 80's and 90's in which drug users prevailed. Other series of non-HACEK Gram negative IE did not show a predominance of S.marcescens nor of P.aeruginosa; E.coli and K.pneumoniae figure more frequently or just as frequently as these do (25,(27)(28)(29)(30)(31)(32)(33)(34). Although it is positive to stimulate clinicians to think of IE and pursue the diagnosis with TOE or PET CT, this will add a great deal of cost and invasive procedures.…”
Section: Gphysical Examination Criteriamentioning
confidence: 97%
“…Serratia marcescens and Pseudomonas aeruginosa, although not rare in BSI, are uncommon causes of IE. Non-HACEK Gram negative IE represents approximately 2% to 6% of all cases of IE, and has been associated with healthcare, including urinary tract procedures, intravenous lines and early prosthetic valve IE (25). However, a recent study across 13 hospitals in Pennsylvania, USA (26), identified 123 cases through electronic records between April 2010 and December 2021, and found a high proportion of intravenous drug users (52%) and of S.marcescens, similar to older series from the 80's and 90's in which drug users prevailed.…”
Section: Gphysical Examination Criteriamentioning
confidence: 99%